2021
DOI: 10.1002/jgc4.1428
|View full text |Cite
|
Sign up to set email alerts
|

Public perceived knowledge of, attitude toward, and use of genetic testing in urban China

Abstract: Because most research about laypeople and genetic testing (GT) has been conducted in other nations than China, we conducted a study in urban China (a) to determine the perceived knowledge of, attitude toward, and use of GT there; (b) to identify influencing factors associated with the public's perceived knowledge, attitudes, and use of GT; and (c) to explore the relationship among public knowledge of, attitude toward, and use of GT. Our data came from a community-based survey in urban Dalian of 868 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
1
1
Order By: Relevance
“…Remarkably, participants with chronic disease had good knowledge scores; this could be explained by the fact that sick people are straining to seek more medical information than healthy ones. The opposite was found in other studies, which showed that participants with poor or fair health have lower levels of awareness about genetic testing than those with good health[ 27 , 28 ].…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Remarkably, participants with chronic disease had good knowledge scores; this could be explained by the fact that sick people are straining to seek more medical information than healthy ones. The opposite was found in other studies, which showed that participants with poor or fair health have lower levels of awareness about genetic testing than those with good health[ 27 , 28 ].…”
Section: Discussioncontrasting
confidence: 61%
“…Regarding the attitude, most participants were willing to perform genetic testing if any family member was diagnosed with a genetic disease, which was in line with the growing body of studies worldwide supporting a positive attitude among populations toward genetic testing [ 29 , 30 ]. Despite the positive attitude toward genetic testing, only a minority of our participants took part in the Emirati genome project; a similar attitude was noticed in the (Qun Wang1 et al) study in China, where 45% of the participant detained positive views toward genetic testing, but only 4% have used it [ 28 ].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation